Aflatoxin free groundnuts: How to bring it to your table - Khaemba, C.; Kitoto, V.; Rutsaert, P.; Muindi, P.; Mbugua, A. (2024)
CIMMYT and partners are advancing gene-edited groundnut varieties with genetic resistance to Aspergilli infection and aflatoxin contamination to reduce aflatoxin levels and increase exports. Nigeria and Malawi, major groundnut producers, allow gene editing technologies. A feasibility study examined how best to introduce these varieties into the value chain and their potential impact on farming. The study compared seed production, farming, processing, and sales in Nigeria and Malawi, with aflatoxin issues more prominent in Malawi. In both Nigeria and Malawi, the seed systems are still in development, however, in Malawi, the seed system is more advanced as it is highly influenced by the private sector and is a value chain system while in Nigeria the seed system is a supply chain system and relies on government. Future scenarios provide the potential entry points for this genetic innovation on aflatoxin. With the two countries posing different entry points. Malawi’s private sector is a potential pathway whereas Nigeria’s government sector is a potential pathway. The new varieties must also meet local preferences for production, color, oil content, and disease resistance.